Methylation-mediated silencing and tumour suppressive function of hsa-miR-124 in cervical cancer - Wilting, Saskia M (BioMed Central, 2010)
BACKGROUND: A substantial number of microRNAs (miRNAs) is subject to epigenetic silencing in cancer. Although epigenetic silencing of tumour suppressor genes is an important feature of cervical cancer, little is known about epigenetic silencing of miRNAs. Since DNA methylation-based silencing of hsa-miR-124 occurs in various human cancers, we studied the frequency and functional effects of hsa-miR-124 methylation in cervical carcinogenesis. RESULTS: Quantitative MSP analysis of all 3 loci encoding the mature hsa-miR-124 (hsa-miR-124-1/-2/-3) showed methylation in cervical cancer cell lines SiHa, CaSki and HeLa as well as in late passages of human papillomavirus (HPV) type 16 or 18 immortalised keratinocytes. Treatment of SiHa cells with a demethylating agent reduced hsa-miR-124 methylation levels and induced hsa-miR-124 expression. In HPV-immortalised keratinocytes increased methylation levels were related to reduced hsa-miR-124 expression and higher mRNA expression of IGFBP7, a potential hsa-miR-124 target gene. Ectopic hsa-miR-124 expression in SiHa and CaSki cells decreased proliferation rates and migratory capacity. Combined hsa-miR-124-1 and/or hsa-miR-124-2 methylation analysis of 139 cervical tissue specimens showed an increasing methylation frequency from 0% in normal tissues up to 93% in cervical carcinomas. Increased methylation levels of hsa-miR-124-1 and hsa-miR-124-2 were significantly correlated with reduced hsa-miR-124 expression in cervical tissue specimens. Combined hsa-miR-124-1 and/or hsa-miR-124-2 methylation analysis of 43 cervical scrapes of high-risk HPV positive women was predictive of underlying high-grade lesions. CONCLUSIONS: DNA methylation-based silencing of hsa-miR-124 is functionally involved in cervical carcinogenesis and may provide a valuable marker for improved detection of cervical cancer and its high-grade precursor lesions.